Regional Uptake and Variations in Orthopaedic Enhanced Recovery Pathways in Knee and Hip Total Arthroplasty. Issue 5 (May 2016) - Mawdsley, MJ; Baker, PN; Desai, A; Green, RN; Jevons, L
The use of enhanced recovery (ER) pathways for hip and knee arthroplasty has increased over the last decade, and the adoption within orthopaedics is becoming more common. We have demonstrated a regional variation and institutional inconsistency of uptake and delivery of ER pathways in our region. Units that have a unified pathway were more likely to have consistency in treatment and early analgesia for patients. We would advocate that units use an agreed enhanced recovery pathway to optimise patient recovery from hip and knee arthroplasties.